Integrated environmental analysis of the main cork products in southern Europe (Catalonia – Spain) - Rives, Jesús; Fernandez-Rodriguez, Ivan; Rieradevall, Joan; Gabarrell, Xavier (Journal of Cleaner Production)
This study presents an environmental analysis of the cork sector by integrating and evaluating the production of the products that are most commonly made of cork: natural cork stoppers, champagne cork stoppers, white cork granulate and black cork granulate, in order to propose environmental strategies that could contribute to minimising the potential impacts of the cork sector. Life Cycle Assessment (LCA) was the methodology used in order to assess the potential environmental impacts of the cork sector and its main products. Inventory was supported by 15 companies in Catalonia. Different environmental midpoint impact categories were reported and analysed according to CML 2001 method such as Abiotic Depletion (ADP), Acidification Potential (AP), Eutrophication Potential (EP), and many other. Also, the Global Warming Potential (GWP 100 years), was assessed, and it was found that the cork sector contributed to fixing carbon dioxide and consequently can help to mitigate climate change, besides generating cork products. Specifically, 3.4 tonnes of CO2 eq. were emitted to convert a tonne of raw cork from the forest into products, while 18 tonnes of CO2 are fixed per tonne as a result of the existence of cork oak forests; the resulting balance was that 14.6 tonnes of CO2 are fixed. A sensitivity analysis was carried out of the distribution of environmental impacts between products; it was observed that allocation rules were an important point of the assessment. The use of cork, a natural, renewable and local material, can help to reduce the environmental impact of products. The use of cork stoppers contributes to reducing the carbon footprint of beverages such as wines, champagnes, beers, ciders, brandies and many other beverages.
Keywords: agro-forestry system; Carbon dioxide; Champagne cork stopper; Cork sector; Environmental impact; Life cycle assessment (LCA); Mediterranean; natural cork stopper

Environmental analysis of raw cork extraction in cork oak forests in southern Europe (Catalonia--Spain). - Rives, Jesús; Fernandez-Rodriguez, Ivan; Rieradevall, Joan; Gabarrell, Xavier (Journal of environmental management, 2012)
Cork oak grows endemically in a narrow region bordering the western Mediterranean, and especially in the Iberian Peninsula. The importance of cork agro-forestry systems lies in the fact that a natural and renewable raw material - cork - can be extracted sustainably without endangering the tree or affecting biodiversity. This paper describes an environmental analysis of the extraction of raw cork in cork oak forests in Catalonia, using data from five representative local forest exploitations. The evaluation was carried out using life cycle assessment (LCA) methodology, and all the forestry management required to obtain a tonne of raw cork was included. The aim of the study was to evaluate the environmental impacts - in terms of global warming, acidification, eutrophication, human toxicity, and so on - caused by cork extraction and determine the carbon dioxide balance of these forestry systems, with a tree lifespan of about 200 years. During the life cycle extraction of cork in Catalonia, 0.2 kg of CO(2) eq. was emitted per kg of raw cork extracted. Moreover, cork cannot be extracted without the tree, which will be fixing carbon dioxide throughout its technological useful life (200 years), despite the fact that the bark is removed periodically: every 13-14 years. If the emission from extraction and the carbon contained in the material is discounted, the carbon dioxide balance indicates that 18 kg of CO(2) are fixed per kg of raw cork extracted. Therefore, cork is a natural, renewable and local material that can replace other non-renewable materials, at local level, to reduce the environmental impacts of products, and particularly to reduce their carbon footprint.
Keywords: agro-forestry system; Carbon dioxide; Climate change mitigation; Cork Oak Forest; Life cycle assessment (LCA); Mediterranean